Karakteristik Penyalaan Droplet Minyak Biji Bunga Matahari Dengan Penambahan Karbon Aktif Kulit Pinang - Ulwan, Abdullah; Riupassa, Helen; Mini, Marthina; Suyatno, Suyatno (Fakultas Teknik UMSU, 2025)
This study aims to reveal the role of biocatalysts based on activated biocarbon from areca nut shell waste in improving the ignition performance of sunflower seed oil droplets as an alternative fuel. Sunflower seed oil, which is rich in unsaturated fatty acids, has strong intermolecular binding forces that slow down its ignition. To overcome this, biocatalysts from activated areca nut shells were used. FTIR analysis showed an increase in the ability of fuel molecules to absorb heat, while TEM studies revealed that biocarbons have high porosity and uniform particle distribution, which supports combustion efficiency. Observations of temperature and droplet evolution using thermocouples and high-speed microscope cameras showed a significant increase in the ignition rate. The results indicate that this biocatalyst not only improves ignition efficiency but also utilizes organic waste, making it an environmentally friendly and sustainable fuel solution.